Boosting Rice Production Through Narrowing of Exploitable Yield Gap - Hossain, MB (SAARC Journal of Agriculture, 2021)
The yield gap discussed in this paper is the difference between the potential farm yield and the actual average farm yield of rice is 1.92 t ha-1 in Bangladesh. The yield gap is mainly caused by physical, biophysical, socioeconomic and institutional factors. Different strategies, such as integrated crop management (improve adapted varieties, site specific nutrient management, locally adapted integrated weed management and optimized water management) practices, timely supply of inputs including credit to farmers, research and extension collaboration to transfer the new technologies have been discussed to minimize yield gap. Suggestions have been made to make credit available to resourcepoor small farmers to buy necessary inputs, reducing transaction cost, simplifying lending procedures and strengthening monitoring mechanism of the current credit system are, however, essential to enable the farmers to avail the credit facility. Efforts should be made to update farmers’ knowledge on the causes of yield gaps in crops and measures to narrow the gaps through training, demonstrations, field visits and monitoring by extension agencies to achieve high yield. Based on present yield gap of rice (1.92 t ha-1) at least Tk. 556 billion could be earned from the additional production annually by narrowing 40 % the yield gap. SAARC J. Agri., 18(2): 167-180 (2020)